MENINGKATKAN KETERAMPILAN BERBICARA MELALUI MODEL PEMBELAJARAN PAIRED STORYTELLING PADA SISWA KELAS V SDN CIPINANG CEMPEDAK 04 - Fadiyah, Hasnah; Yarmi, Gusti; Amir Soleh, Dudung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Speaking skills, particularly storytelling, are a crucial aspect of Indonesian language learning; however, fifth-grade students at SDN Cipinang Cempedak 04 still face challenges such as the incorrect application of language rules, difficulties mastering linguistic and non-linguistic elements, and a lack of self-confidence when telling stories in front of the class. This study aims to improve the speaking (storytelling) skills of fifth-grade students through the implementation of the Paired Storytelling learning model. The study employed a classroom action research method based on the Kemmis and McTaggart model, conducted over three cycles, each comprising planning, action implementation, observation, and reflection stages. The research subjects were 28 students from class VB, with the class teacher acting as an observer-participant. Data were collected through observations of learning activities and speaking skill tests using assessment rubrics, then analyzed using descriptive statistics (percentage calculations). The results showed an increase in teacher activity from 83.3% in Cycle I to 96.67% in Cycle III, and student activity from 75% to 93.3%. Student mastery of speaking skills improved from 28.6% (with an average score of 69.2) in Cycle I to 71.4% (average 80.4) in Cycle II, reaching 100% (average 85.3) in Cycle III. It can be concluded that the implementation of the Paired Storytelling model is effective in enhancing the speaking skills of fifth-grade elementary school students.